Funkcje żłobków polskich od początku XX wieku do wybuchu II wojny światowej - Świdrak, Ewelina (Biuletyn Historii Wychowania, 2019)
The issue of institutional care of the youngest children has been rarely discussed in scientific studies. In the context of the contemporary debates about improving the quality of toddlers’ care and education, it is a good idea to remind about the origin of nurseries and the development thereof. The first nurseries were established in Poland over 100 years ago. From the beginning, before Poland even regained independence until present day, they have changed their functions and organization. The aim of the article is to show the changes to the function of crèches against a political, social and cultural background since the very beginning of the existence of nurseries until the outbreak of World War II. The method used in this article is historical explanation, and the technique is an analysis of documents: literature, magazines, legal acts. The responsibilities of crèches discussed in this article include care, health -related, educational, upbringing and family-related activities This is the first of two articles related to changes in the function of crèches in a historical approach.